Time to Drug-Resistant Tuberculosis Treatment in a Prospective South African Cohort - Brittney J. van de Water PhD; Janet Prvu Bettger ScD; Susan Silva PhD; Janice Humphreys PhD; Coleen K. Cunningham MD; Jason E. Farley PhD, MPH (SAGE Publishing, 2017)
This study examined time to treatment initiation by age among a prospective cohort with drug-resistant tuberculosis (DR-TB). Participants aged 13 years or older nested within a cluster-randomized trial in 2 South African provinces were evaluated. Outcomes were treatment initiation within 5 days of DR-TB diagnosis (National Tuberculosis Program guidelines) and days from diagnosis to treatment. A total of 521 participants met inclusion criteria. Eighty-two patients (16%) met national guidelines; median time to treatment was 11 days (range = 0-180). No patient (age, sex, prior TB history, HIV status) or health system characteristics (geographic urban/rural location, province) were associated with treatment initiation per guidelines except geographic location ( t = 3.64, degrees of freedom = 1, P = .0003). One in 6 individuals with DR-TB received treatment per guidelines, and average time to treatment was 11 days. Strategies are needed to decrease treatment delays and meet the recommended guidelines for treatment for patients of all ages.